Effects of a basic skills program in the social development of children diagnosed with dysphasic type expressive-comprehensive language disorder that belong to a lower socioeconomic status - Dioses Chocano, Alejandro S. (2001)
Presently study was elaborated and it executed a program dedicated to increase the basic abilities of 14 children diagnosed with dysfunction of the expressive language understanding of dysphasic type, assisted in the C1inic of Social Projection of the Peruvian Center of Audition, Language and Learning. The one mentioned program included the areas of attention, pursuit of instructions and imitation. Three evaluations were made with the Scale of Social Maturity of Vineland, the same ones that allowed to appreciate an increment in the global punctuation of the social development of each one of the participants, the same ones that however, they didn't go significant when being analysed the social age and the corresponding category. Is considered that a work of more time would allow to obtain better, achievements in the abilities worked in reason of the observed tendency, in the same way, a considerable impact has been generated in the improvement of the quality of the children`s life and its families, the same one that is evidenced in a remarkable improvement of the relationships between these children and its respective parents,